Modelling magnetic characteristics of steel secondary of a linear induction motor - Kürüm, Hasan; Altun, Hüseyin; Guldemir, Hanifi (My University, 2002)
In this paper, electrical and magnetic characteristics of the secondary material of a constructed model linear induction motor (LIM) with solid iron secondary disc have been experimentally obtained. For obtaining the magnetic characteristics of the secondary material a torus has been constructed from the same material on which a toroidal coil has been wound. The B-H characteristics of this torus has been determined experimentally. For consideration the magnetic characteristics of this secondary material in the calculations, a mathematical B-H characteristic has been modeled by using those results obtained from experiment.
Modeliranje magnetskih karakteristika ?elika sekundarnog namota linearnog indukcijskog motora
Keywords: B-H characteristic; Linear induction motor; Magnetic conductivity; Magnetic reluctivity